Time-dependent rheological behavior of cement-sand injection grout containing high volume fly ash. Issue 1 (May 2020) - Balakrishnan, B; Khalid, N H A; Ismail, M
Abstract: Grouting technology is playing an increasingly important role in construction engineering. Various types of grout are available but cement slurry grouts are often selected for injection works due to better workability. Meanwhile, in repair works, cement-sand grout often preferred as the fine aggregates gives better volume stability for large repair area. However, theoretical research on the use of waste material to improve the rheological properties of cement-sand grout is still lacking. For grouts, rheology is a factor of prime importance to the transport, injection and pumping of the material. Cement-sand grouts often have poorer fluidity due to friction created by the sand. Since grouts typically contain cement, therefore fly ash can be a good option to improve the workability of the grout. This paper studies time dependent behaviour of the grout by measuring the flow times and viscosity of cement-sand grout containing high volume fly (HVFA) up to 1 hour from the time of mixing. The result indicates that replacement of HVFA reduces the flow time of the grout and maintained good fluidity up to 1 hour. The viscosity test showed that the grouts, at fresh state, behaved like a Bingham fluid by exhibiting lower viscosities for the mixtures containing fly ash at 0, 60 and 120 minutes. In conclusion, the use of large quantities of fly ash in grouts significantly enhances fluidity of the cement-sand grouts. Methodology comparison also resulted in new knowledge for best method flow test for fly ash grout.